An overview of the archaeological theory in Peru in the early Twenty-first Century. - Tantaleán, Henry (2020)
In this article, we present an overview of the archaeological theory developed in Peru in the last two decades. For that purpose, first, the place and nature of the theory in Peruvian archaeological practice is considered. Secondly, the political and economic contexts in which the archaeological practice of recent years has developed are briefly described. Third, an outlook of the archaeological theories used in our country is described, focusing on the main developed topics of study. Fourth, other relevant theoretical topics that have been developed in Peruvian archaeology are reviewed. Finally, some issues that deserve further theoretical development in Peruvian archaeology are introduced.